Progress in Cardiac Magnetic Resonance Feature Tracking for Evaluating Myocardial Strain in Type-2 Diabetes Mellitus - Shen, Li-Ting; Shi, Rui; Yang, Zhi-Gang; Gao, Yue; Jiang, Yi-Ning; Fang, Han; Min, Chen-Yan; Li, Yuan (Current Diabetes Reviews, 2024)
The global prevalence of type-2 diabetes mellitus (T2DM) has caused harm to human health and economies. Cardiovascular disease is one main cause of T2DM mortality. Increased prevalence of diabetes and associated heart failure (HF) is common in older populations, so accurately evaluating heart-related injury and T2DM risk factors and conducting early intervention are important. Quantitative cardiovascular system imaging assessments, including functional imaging during cardiovascular disease treatment, are also important. The left-ventricular ejection fraction (LVEF) has been traditionally used to monitor cardiac function; it is often preserved or increased in early T2DM, but subclinical heart deformation and dysfunction can occur. Myocardial strains are sensitive to global and regional heart dysfunction in subclinical T2DM. Cardiac magnetic resonance feature-tracking technology (CMR-FT) can visualize and quantify strain and identify subclinical myocardial injury for early management, especially with preserved LVEF. Meanwhile, CMR-FT can be used to evaluate the multiple cardiac chambers involvement mediated by T2DM and the coexistence of complications. This review discusses CMR-FT principles, clinical applications, and research progress in the evaluation of myocardial strain in T2DM.
Keywords: Cardiac magnetic resonance feature tracking